Diagnostic and classification tools for chronic headache disorders: A systematic review. (May 2019) - Potter, Rachel; Probyn, Katrin; Bernstein, Celia; Pincus, Tamar; Underwood, Martin; Matharu, Manjit
Background or aim: Despite guidelines and the International Classification of Headache Disorders (ICHD-III beta) criteria, the diagnosis of common chronic headache disorders can be challenging for non-expert clinicians. The aim of the review was to identify headache classification tools that could be used by a non-expert clinician to classify common chronic disorders in primary care. Methods: We conducted a systematic literature review of studies validating diagnostic and classification headache tools published between Jan 1988 and June 2016 from key databases: MEDLINE, ASSIA, Embase, Web of Knowledge and PsycINFO. Quality assessment was assessed using items of the Quality of Diagnostic Accuracy Studies (QUADAS-2). Results: The search identified 38 papers reporting the validation of 30 tools designed to diagnose, classify or screen for headache disorders; nine for multiple headache types, and 21 for one headache type only. We did not identify a tool validated in a primary care that can be used by a non-expert clinician to classify common chronic headache disorders and screen for primary headaches other than migraine and tension-type headache in primary care. Conclusions: Despite the availability of many headache classification tools we propose the need for a tool that could support primary care clinicians in diagnosing and managing chronic headache disorders within primary care, and allow more targeted referral to headache specialists.